2012
DOI: 10.1111/j.1540-8175.2012.01688.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Mass Index on Left Ventricular Diastolic Dysfunction

Abstract: BMI is an independent predictor of LV diastolic dysfunction along with age, hypertension, and diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 29 publications
1
22
2
3
Order By: Relevance
“…However, in adult subjects, a link has been shown between obesity itself and subclinical cardiac structural changes leading to an "obese cardiomyopathy" syndrome [1]. Several authors have reported associations of obesity with increased left ventricular (LV) wall stress and compensatory LV hypertrophy [2], LV dilation, and even heart failure [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, in adult subjects, a link has been shown between obesity itself and subclinical cardiac structural changes leading to an "obese cardiomyopathy" syndrome [1]. Several authors have reported associations of obesity with increased left ventricular (LV) wall stress and compensatory LV hypertrophy [2], LV dilation, and even heart failure [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most important health problems in the world and is associated with a large spectrum of cardiovascular changes resulting from altered hemodynamics and inflammation (1, 2). Among these changes, left atrial (LA) enlargement and subclinical impairment of left ventricular (LV) function are precursors to more serious forms of cardiac dysfunction and heart failure (3).…”
Section: Introductionmentioning
confidence: 99%
“…Increased BMI is a risk factor for hypertension, diabetes and dyslipidemia, all of which augment the risk of ischemic heart disease, and hypertension and diabetes independently increase the risk of heart failure [5]. In addition, elevated BMI is associated with increased left ventricular (LV) mass [5,6], and altered LV remodeling [6]; however, the association of BMI with diastolic dysfunction is independent of age, hypertension, diabetes and LV mass [1,2]. Other mechanisms by which BMI may impact on diastolic function and risk of heart failure include altered myocardial structure, neurohormonal activation and altered myocardial metabolism [4,7-9].…”
Section: Introductionmentioning
confidence: 99%